Molecular mechanism of Spinocerebellar Ataxia type 6: glutamine repeat disorder, channelopathy and transcriptional dysregulation. The multifaceted aspects of a single mutation - Giunti, Paola; Mantuano, Elide; Frontali, Marina; Veneziano, Liana (Frontiers in Cellular Neuroscience, 2015)
Spinocerebellar Ataxia type 6 is an autosomal dominant neurodegenerative disease characterized by late onset, slowly progressive, mostly pure cerebellar ataxia. It is one of three allelic disorders associated to CACNA1A gene, coding for the Alpha1 A subunit of P/Q type calcium channel Cav2.1 expressed in the brain, particularly in the cerebellum. The other two disorders are Episodic Ataxia type 2, and Familial Hemiplegic Migraine type 1. These disorders show distinct phenotypes that often overlap but have different pathogenic mechanisms. Episodic Ataxia type 2 and Familial Hemiplegic Migraine type 1 are due to mutations causing, respectively, a loss and a gain of channel function. Spinocerebellar Ataxia type 6, instead, is associated with short expansions of a polyglutamine stretch located in the cytoplasmic C-terminal tail of the protein. This domain has a relevant role in channel regulation, as well as in transcription regulation of other neuronal genes; thus the SCA6 CAG repeat expansion results in complex pathogenic molecular mechanisms reflecting the complex Cav2.1 C-terminus activity. We will provide a short review for an update on the Spinocerebellar Ataxia type 6 molecular mechanism.